Penerapan Teknologi Feminisasi Ikan Betok (Anabas testudineus) yang Dipelihara di Kolam Terpal pada Kelompok Pembudidaya Ikan Haru Mangat Kota Palangka Raya - Mohamad Rozik; Ummi Suraya; Muhamad Noor Yasin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Community Service Program (PPM) activities that will be carried out in the Haru Mangat fish farmer group in the form of technology for Betab Cultivation (Anabas testudineus) with an intensive system through the feminization process in the fish, to increase the skills and knowledge of the target audience, while the benefits are to create new micro-businesses for target partners. The method of activities with the method of direct participant observation of the activities of observation and interviews, implementation of training and technical guidance, and demonstration plot demonstration activities. The outputs of the Community Service program activities in the Haru Mangat fish cultivator group especially fish farmers in cultivating Betok fish intensive systems in ponds can easily understand and know the techniques of raising Betok fish with feminization technology. The fish cultivator group is very interested to cultivate it using tarpaulin ponds.